Análise estatística de índices morfométricos e dimensão fractal da vascularização da retina humana - OLIVEIRA, Antônio José de (2006)
The analysis of the fundus of the eye photographic images has permitted the obtaining of an accurate diagnoses for several diseases related to the human retina vascularization. This work proposes the morphormetric analysis and the fractal dimension as methods capable to parameterize the retinal vascular process. A hand made segmentation of the retina vessels done in this work allowed the obtaining of high defined image of the retina vessels. These images made possible the parametrization of the retina vessels using the shape indexes and fractal dimension. The shape indexes like perimeter, area,circularity and rectangularity were used to describe the shape of the tributary venules of the human retina central vein. The statistical analysis showed that both the perimeter and the area of the tributary venules of the central vein of human retina are significantly different between normal and with non proliferative diabetes individuals. But the parameter circularity and rectangularity of these tributary venules were not significantly different. Then,the parameters perimeter and area can be used to discriminate the normal from the ill retina, while the parameters circularity and rectangularity are inadequate to distinguish them. The fractal dimension of the vascularization human retina,in the normal and disease conditions, differed significantly between themselves, independently of the method applied to calculate it.Therefore, the fractal dimension is a parameter which can be used to distinguish the normal from the disease state of the human retina.